Literatura e história em gaúchos no obelisco, de Cyro Martins - Nascimento, Fábio Varela (2014)
This dissertation is about the relationship between literature and history, focusing on the work Gaúchos no obelisco, published in 1984 by the writer and psychoanalyst Cyro Martins. Among its objectives are to analyze the interweaving of literature and history in the work of Cyro Martins, to uncover the techniques used for the history's insertion in the novel and to examine the literary elements present in the narrative. In 1980, Cyro presented, at the Simpósio sobre a Revolução de 1930, a literary text about the historical event. From this theme, this paper is built. At first, thre is an analysis about the presence of history within the narrative through referential aspects such as dates, places, entities and historical characters. After, divided into nucleus, fictional characters are observed. Some of the theorists who subsidize this study are Maria Teresa de Freitas, Alcmeno Bastos, Käte Hamburger, Antonio Candido, Sandra Jatahy Pesavento and Luiz Costa Lima